PENDAMPINGAN PEMBUATAN PERATURAN KAMPUNG DI KAMPUNG TAMBAT DISTRIK TANAH MIRING KABUPATEN MERAUKE - Nurul Widhanita Y. Badilla; Nurlela Pandiangan (Musamus Devotion Journal, 2020)
In accordance with the Village Law, each village is expected to be able to make village regulations to guide the implementation of village development and many village officials make village regulations only as a formality or just as long as they do not pay attention to the procedures for making regulations such as the level of preparation, determination, implementation , assessment and reintegration of the finished product. With all the problems, so that the resulting Village Regulation is not in accordance with the procedures for its formation. The low education of village officials and the lack of understanding of village officials on how to make village regulations and related scientific backgrounds and experience in the field of government also greatly affect the ability and technical skills with their task fields. Of the problems that exist in the village including Tambat village, it is necessary to do training and assistance in making village regulations so that the results produced are in accordance with applicable procedures and in accordance with the criteria for village regulations. The method used in the Training Program is carried out through the Socialization, Training and assistance activities. Formulation of Village Regulation Making is carried out through the Socialization and Training activities and mentoring until the completion of at least 3 Village Regulations. The method used in this service is to provide material, create groups so that each group can make a story, present the results of group work, improve each group's report in accordance with the inputs.